Regional Influences oBusiness Transfers within the British Isles - Geraldine Ryan; Bernadette Power; Noreen McCarthy; Paul Braidford (European Regional Science Association (ERSA), 2010)
Objectives: Business transfers are posing a particular problem for several European countries as the age distribution of business owners rises and as the number of firms transferred within families' declines. This paper explores firm, market, and regional differences in firms which are expected to be transferred in the British Isles against those that are expected to be disposed of. It also examines whether there are regional differences in the types of businesses which are expected to be transferred across the British Isles. Prior Work: Previous research in this area has primarily examined intergenerational succession in family businesses (Bennedsen et al. 2006), while the research into management-buyouts and trade-sales has focused on the entrepreneur's mode of entry (Parker and Van Praag, 2006). Martin et al. (2002) finds evidence that spatial differentiation exists in the vulnerability of firms to age related business transfer failure. In this paper we examine whether businesses located in relatively more economically vibrant regions within the British Isles, whether due to urban economies (Gordon and McCann 2005) or agglomeration economies (Parr 2002) or the level of entrepreneurial talent (Markley, 2006) in the region, have a lower probability of a business transfer failure. Approach: Interview evidence on the expected end-game strategy of entrepreneurs facing the risk of age related transfer failure was obtained from firms in a number of regions in the British Isles, namely the Republic of Ireland, Northern Ireland, Scotland, Wales and England (800 cases). A model is developed which predicts how firm, market and regional characteristics influence whether a firm is expected to be transferred or not. Preliminary Results: Entrepreneurs who expect to dispose of the assets of the business on their retirement have a significantly lower probability of having a high level of entrepreneurial talent in the region and a higher probability of having a high level of GVA per head in the region than entrepreneurs who expect to transfer their businesses. A higher level of entrepreneurial talent (as measured by stock of businesses per resident) and a lower of GVA per head are more likely in rural regions.
Keywords: 330; Entrepreneurial Exit; Small-Medium Enterprises; Regional Differences; Multinomial Probit Model